2023
DOI: 10.3390/biom13071074
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E (ApoE) Rescues the Contractile Smooth Muscle Cell Phenotype in Popliteal Artery Aneurysm Disease

Abstract: Popliteal artery aneurysm (PAA) is the most frequent peripheral aneurysm, primarily seen in male smokers with a prevalence below 1%. This exploratory study aims to shed light on cellular mechanisms involved in PAA progression. Sixteen human PAA and eight non-aneurysmatic popliteal artery samples, partially from the same patients, were analyzed by immunohistochemistry, fluorescence imaging, Affymetrix mRNA expression profiling, qPCR and OLink proteomics, and compared to atherosclerotic (n = 6) and abdominal aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Recent single-cell transcriptome evidence demonstrated that ApoE + macrophages presented with overwhelming infiltration in some IA, and macrophage-derived ApoE potentially served as a biomarker to distinguish IA in molecular pathology ( 23 ). In vascular diseases, ApoE has been reported to reduced smooth muscle cells proliferation and be involved in phenotypic remodeling ( 24 ). As a lipid transport molecule, the ApoE relevant lipid efflux is a feature of peripheral vascular structural variations and aneurysm lesions ( 25 , 26 ).…”
Section: Macrophages Recruitment and Activation In Iamentioning
confidence: 99%
“…Recent single-cell transcriptome evidence demonstrated that ApoE + macrophages presented with overwhelming infiltration in some IA, and macrophage-derived ApoE potentially served as a biomarker to distinguish IA in molecular pathology ( 23 ). In vascular diseases, ApoE has been reported to reduced smooth muscle cells proliferation and be involved in phenotypic remodeling ( 24 ). As a lipid transport molecule, the ApoE relevant lipid efflux is a feature of peripheral vascular structural variations and aneurysm lesions ( 25 , 26 ).…”
Section: Macrophages Recruitment and Activation In Iamentioning
confidence: 99%
“…Compared with AAA, little is known about the specific pathogenesis of PAAs despite the popliteal artery being of a muscular rather than an elastic type [5,6]. However, the clinical presentation and symptoms differ.…”
Section: Introductionmentioning
confidence: 99%